Forms of Expert Knowledge Application in Land Disputes Settlement - O. V. Zhukova (Теория и практика судебной экспертизы, 2019)
When considering land disputes, a court examines a large amount of evidence. In this forensic land survey expertise has taken a special place since its findings often form the basis of the court decision. The correct and prompt consideration of the dispute depends on the quality work of an expert.The paper reviews a range of problems emerging when appointing a land survey expertise, preparing materials for the forensic examination, assessing forensic expert opinions and other evidence by the court. Inter alia, it is essential to correctly determine the type of examination, the list of necessary documents to conduct it, to estimate the duration of the study. The author reveals the possibilities of expansion of a specialist’s advisory activities at the expertise appointment stage to reduce the time of its conduct.